Off-label use of inhaled bronchodilators in hospitalised patients in Spain: a multicentre observational study. (24th April 2020) - Villamañán, Elena; Sobrino, Carmen; Bilbao, Cristina; Fernández, Jaime; Herrero, Alicia; Calle, Myriam; Alvaro, Dolores; Segura, Maria; Picazo, Gracia; Rodríguez, José Miguel; Baldominos, Gema; Ramirez, Maria Teresa; et al.
Abstract : Background: Off-label prescription of inhaled bronchodilators (IB) is frequent, despite the fact that they can be ineffective and increase avoidable healthcare costs. Objective: To analyse the frequency of off-label prescription of IB in hospitalised patients. Indications and level of evidence, involved drugs, medical specialties prescribing off-label IB and patients' adherence to IBs were also evaluated. Method: A descriptive, observational, cross-sectional study was performed in four tertiary hospitals in Spain. The main outcome measure was the number of patients prescribed off-label IBs. Prescriptions were checked against the European Medicines Agency-approved indications. The level of evidence supporting off-label prescription of IBs (according to MICROMEDEX 2.0) was also analysed. Patients were interviewed to test differences (off-label vs on-label) in adherence and knowledge about their inhaled therapy. Results: 217 patients were prescribed IBs, 92 of whom were givend off-label IBs (54.7% men, mean age 73.9±12.9 years). The most common off-label prescriptions for IBs were: unspecified dyspnoea (not related to COPD or asthma) (27.2%), respiratory infections (23.9%) and heart failure (22.8%). 76.8% of patients did not have evidence supporting them. Beta2 -agonist+corticosteroids and anticholinergics were most commonly prescribed off-label. Internal Medicine was the main medical specialty involved. There were no differences between off-label and on-label users in terms of patients' knowledge about treatment and adherence. Conclusion: Off-label indications for IBs are common in hospitalised patients and are generally indicated without scientific support. Dyspnoea not related to COPD or asthma, respiratory infections and heart failure were the main off-label indications, most frequently treated with anticholinergics and beta2 -agonists+corticosteroids, for which their efficacy and safety has not been proved. Our results show that prescribing needs to be improved to follow the evidence that exists. Moreover, further research focused on off-label indications is needed to clarify whether they are effective, safe and cost-effective.